La Création Et La Vénération Des Saints Au Maroc - Lahoucine, Aguinou (European Scientific Journal, ESJ, 2018)
This article, which is part of social and religious relations, tries to study the sainthood and the cult of saints in Morocco. In order to achieve the objective of this work, we adopt an empirical method, which is based essentially on documentary research. To analyze the cult of saints in Morocco, this article presents, at first, the definitions of the words " sainthood " and " saint ". Then, the different appellations used byMoroccan people to designate a saint, and the types of existing saints in the Kingdom. Finally, the reasons for which these saints are created and venerated.